2002
DOI: 10.1590/s0102-35862002000600005
|View full text |Cite
|
Sign up to set email alerts
|

Estudo de correlação entre provas funcionais respiratórias e o teste de caminhada de seis minutos em pacientes portadores de doença pulmonar obstrutiva crônica

Abstract: ARTIGO ORIGINAL

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
9

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 16 publications
(19 reference statements)
0
8
0
9
Order By: Relevance
“…Apesar de o tempo no TEsc com EV ser menor, não se pode descartar o efeito aprendizado, sendo interessante novos estudos com aplicação de vários TEsc com EV para se esclarecer esse efeito, semelhante ao realizado com o TC6 2,[15][16][17] . Na padronização do TC6, houve preocupação com a utilização do estímulo verbal 2 , motivado por estudos que mostraram que o estímulo verbal pode aumentar a distância percorrida em até 30 metros 3,4 e assegura máxima motivação e performance do indivíduo 2,18,19 . Os resultados encontrados nesse trabalho mostraram que o EV também é fundamental para o resultado do TEsc.…”
Section: Resultsunclassified
“…Apesar de o tempo no TEsc com EV ser menor, não se pode descartar o efeito aprendizado, sendo interessante novos estudos com aplicação de vários TEsc com EV para se esclarecer esse efeito, semelhante ao realizado com o TC6 2,[15][16][17] . Na padronização do TC6, houve preocupação com a utilização do estímulo verbal 2 , motivado por estudos que mostraram que o estímulo verbal pode aumentar a distância percorrida em até 30 metros 3,4 e assegura máxima motivação e performance do indivíduo 2,18,19 . Os resultados encontrados nesse trabalho mostraram que o EV também é fundamental para o resultado do TEsc.…”
Section: Resultsunclassified
“…At our study, the initial distance walked by patients during the six-minute walk test was 336±76.36 m, while the average of the final distance walked by patients was 402.76±51.29 m. That is, these patients gained functional capacity, which reflects positively on their daily life activities, on aerobic capacity to practice activities, and on functional status of the cardiovascular and/or respiratory system as well as on morbidity and mortality indexes 28 . For this parameter it is possible to monitor the effectiveness of treatment and establish the prognosis of these individuals 29 . It can be observed that in a short time it is possible to obtain favorable results through the Russian current electrical stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…For MEP (maximal expiratory pressure) a maximal oral inspiration was performed followed by a complete expiration following the criteria indicated by Rodrigues and Veigas 12 . Measurements of MIP and MEP were performed three consecutive times, with intervals of one minute to rest, and the highest value obtained was considered for analysis.…”
Section: Methodsmentioning
confidence: 99%